Effect of growth rate and pH on Li isotope fractionation during its incorporation in calcite. (15th April 2022) - Füger, A.; Kuessner, M.; Rollion-Bard, C.; Leis, A.; Magna, T.; Dietzel, M.; Mavromatis, V. B. Μαυρομάτης
Abstract: Lithium isotope compositions were determined for synthetic calcite and fluid, reported in Füger et al. (2019) . Calcite was precipitated at 25 °C, and mineral growth rate and pH varied within the range of 10 −8.1 ≤ rp (mol m −2 s −1 ) ≤ 10 −7.2 and 6.3 ≤ pH ≤ 9.5, respectively. At pH = 8.25 ± 0.15, the Δ 7 Licalcite-fluid = δ 7 Licalcite - δ 7 Lifluid value of −2.76 ± 0.22‰ (n = 4) was yielded when calcite growth rate was lower than ∼ 10 −7.7 (mol m −2 s −1 ). As calcite growth rate increased, Δ 7 Licalcite-fluid values progressively decreased to about −4.5‰. The dependence of Li isotope fractionation on calcite growth rate is described by the surface reaction kinetic model developed by DePaolo (2011). In this model the equilibrium and kinetic isotope fractionation factors obtain values of −2.7 ± 0.1‰ and −8.8 ± 0.1‰, respectively. In addition, for experiments performed under similar surface-normalized growth rate of 10 −7.7±0.2 (mol m −2 s −1 ) a significant decrease in Δ 7 Licalcite-fluid from pH 9.5 to 6.3 was observed. These variations of Δ 7 Licalcite-fluid as a function of pH for experiments performed under low degrees of solution saturation with respect to calcite point towards the incorporation of two or more Li-bearing species in the solid phase. Thus, the Li isotope composition of the solid reflects the abundance of these species, which depends on solution pH and fluid composition. Overall the results of this study suggest that both calcite growth rate and pH are parameters that can significantly affect the measured Li isotope fractionation between calcite and fluid. The high sensitivity of Δ 7 Licalcite-fluid to calcite growth rate observed in this study suggests that a high variability of δ 7 Licalcite in natural samples, such as foraminifera, brachiopods, and speleothems can be expected in natural environments. The implications for the potential use of elemental and isotope fractionation of Li during calcite formation are discussed in the light of reconstruction of paleo-environmental conditions.